Exponential Stability for Multi‐Area Power Systems with Time Delays Under Load Frequency Controller Failures. Issue 2 (24th August 2016) - Li, Xu; Wang, Rui; Wu, Shu‐Nan; Dimirovski, Georgi M.
Abstract: This paper investigates the exponential stability problem for a class of multi‐area power systems with time delays under load frequency controller failures (LFCFs). For describing the phenomenon of LFCFs, the considered multi‐area power system is rewritten as a switched system with multiple time delays. By adopting the switching technique, the exponential stability conditions for multi‐area power systems are developed when the controller failure frequency and the unavailability ratio of the controller are restricted. Finally, one example is given to show the applicability of the proposed method.